SCHIMBARI GEOGRAFICE ÎN PERIOADA TRANZIŢIEI ŞI PROBLEMELE MUNICIPIULUI ALBA IULIA ÎN RAPORT CU ROLUL ŞI POZIŢIA ÎN REŢEAUA URBANĂ ACTUALĂ (PANGEEA, 2025)
By the role and position within the national and county urban network, Alba Iulia city is an important urban ensemble in the large passage of the Mureş river, at the crossroads of major units of relief, where the city expansion and its functional areas have generated a specify binuclear and radial-tentacle structure of city street, along his major transport axes. The street configuration in relation  to functional zoning of the city and its problems, as well as restrictive limits, have generated a specific urban traffic, which highlights major traffic arteries and areas of the city, certain points of connection to the national grid, a series circulation problems and other issues that affect the life and work of urban residents.